Computational fluid dynamics approach for analyzing static statistics of Hyperloop transportation - Hartapan Singh; Harminder Singh; Himanshu Khanna (Journal of Engineering and Applied Science)
Abstract The computational fluid dynamics (CFD) technique helps analyze the static and dynamic characteristics of Hyperloop transportation systems. Hyperloop systems are a novel transportation approach with high-speed, low-pressure tubes for passenger and cargo transportation. They offer remarkable speed capabilities, energy efficiency, and minimal noise and emissions. Hyperloop systems promise reduced travel times between cities. CFD simulations examine Hyperloop performance in various scenarios, including structural, aerodynamic, and thermal factors. In this study, we used CFD models to assess a Hyperloop pod vehicle, looking at static and dynamic results at speeds of 500 km/h, 700 km/h, and 900 km/h. The study examines pressure, velocity, drag, and the geometry of the vehicle pod in a tunnel environment. Experimental experiments were performed in an enclosed area of a 10-m-long pipe, with the vehicle having a radius. The tunnel’s parameters were varied by varying the blockage ratio, corresponding to the vehicle’s cross-sectional area ratio to the total tunnel area from the symmetry line to the square. We improved the blockage ratio using CFD simulations, providing detailed insights into pressure conditions upstream and downstream of the vehicle pod. CFD simulations play a pivotal role in ensuring these innovative transportation networks’ safety, energy efficiency, and environmental friendliness.